The significance of mountain glaciers as sentinels of climate and environmental change. Issue 6 (June 2017) - Mark, Bryan G.; Fernández, Alfonso
Abstract: Mountain glaciers are transient hydrologic reservoirs persisting at the habitable extremes of Earth that both document and respond to climate change. They withhold water in solid phase from other reservoirs and ultimately impact sea levels. Moreover, they are valued resources with economic and cultural significance for human societies living below them. They also preserve histories of past climates. Yet, when climate change forces glaciers to lose mass, the water and suspended matter flow downstream with various impacts. Profoundly, current glacier and environmental changes are now accelerating and being propelled by human activity. Diverse consequences of these changes are emerging, and many are negative for society. Nevertheless, these changes coincide with a time in human history during which science is able to observe changes with unprecedented detail. Geography has a key role to play in analyzing the patterns and impacts of mountain glacier changes over multiple spatial and temporal scales and involving an integrated approach that draws on different disciplines and innovative technology to account for interactions between multiple spheres of the Earth System.